The complement system and its role in the treatment of ANCA-associated vasculitis - Rybak, Natalia; Dudek, Iga; Czarnota, Jakub; Dobrzyński, Michał; Skubel, Tomasz; Drozd, Małgorzata (Journal of Education, Health and Sport, 2022)
Objective: This study aimed to evaluate the role of the complement system in a therapy of the ANCA- associated vasculitis. Methods and materials: A literature search was conducted in the PubMed MEADLINE database of medical publications using the following keywords: the complement system, AVV, C5a inhibitor, avacopan Results: The complement system is a crucial part of the human immune system. Its cascade is involved in the pathogenesis of many disease entities, especially those with an inflammatory response. As anaphylatoxin, this is especially true of the C5a protein. C5a receptors are distributed mainly on tissue inflammatory cells, e.g. macrophages, mast cells, and endothelial cells. Therefore a C5a receptor inhibitor may reduce the inflammatory response of the body. This mechanism is used by the Avacopan, a newly approved drug for the treatment of ANCA-associated vasculitis as the main indication. Tavneos (avacopan) was only introduced in the UE in January 2022, as the first new drug to treat AVV in over a decade. Conclusion: The C5a receptor inhibitor – Avacopan might be the future of a glucocorticoids-free or glucocorticoids – low dose therapy of ANCA-associated vasculitis. As the ADVOCATE clinical trial shows, Avacopan was neither superior, nor inferior to prednisone tamper with respect to sustained remission at 26 weeks, but proved to be superior with sustaining remission at 52 weeks. All the patients received rituximab or cyclophosphamide as a form of therapy. Keywords: the complement system; C5a receptor inhibitor, AVV; Avacopan